2019
DOI: 10.5465/amj.2017.0054
|View full text |Cite
|
Sign up to set email alerts
|

Structuring Reality Through the Faultlines Lens: The Effects of Structure, Fairness, and Status Conflict on the Activated Faultlines–Performance Relationship

Abstract: Structuring reality through the faultlines lens: the effects of structure, fairness, and status conflict on the activated faultlines-performance relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 132 publications
(175 reference statements)
1
56
0
Order By: Relevance
“…Diversity practices focused on enhancing staff development and professional success broadly are likely to have very different consequences compared to those seen as benefiting just a few (Rousseau, ). The nature and implementation of such practices can vary in terms of the workplace fairness they generate (e.g., Nishii, ), and the effect of justice perceptions on diminishing faultline activation (e.g., Antino, Rico, & Thatcher, ).…”
Section: Discussionmentioning
confidence: 99%
“…Diversity practices focused on enhancing staff development and professional success broadly are likely to have very different consequences compared to those seen as benefiting just a few (Rousseau, ). The nature and implementation of such practices can vary in terms of the workplace fairness they generate (e.g., Nishii, ), and the effect of justice perceptions on diminishing faultline activation (e.g., Antino, Rico, & Thatcher, ).…”
Section: Discussionmentioning
confidence: 99%
“…Research on faultlines has been demonstrating negative effects of faultlines on team outcomes, even if they are dormant (Thatcher & Patel, 2012). However, activated faultiness have a larger impact on outcomes (e.g., Antino, Rico, & Thatcher, 2018) than the dormant. According to SIT, the most negative consequence of in-group and out-group dynamics is the lack of intersubgroup communication (Hogg, 2001) that might stifle team innovation.…”
Section: Team Innovationmentioning
confidence: 99%
“…Faultline research examines the alignment of two or more types of diversity in a team, such as gender and culture or nationality and function (Lau & Murnighan, 1998. In general, research has found that faultlines tend to moderate relationships between diversity and outcomes, such that any negative impact of diversity is more negative when faultlines are ''activated,'' or perceived as salient by the team's members (e.g., Antino, Rico, & Thatcher, 2019;Bezrukova, Spell, Caldwell, & Burger, 2016;Spoelma & Ellis, 2017). In other words, faultlines split groups into ''us'' and ''them,'' and it is difficult for groups to bridge these faultlines.…”
Section: Culture and Cultural Diversity In Teamsmentioning
confidence: 99%